Effectiveness of grouted layer in the mitigation of subway-induced vibrations. (January 2023) - Sadeghi, Javad; Haghighi, Ehsan; Esmaeili, Morteza
As a practical countermeasure against generally destructive subway-induced vibrations, the injection of a continuous thin layer of soft materials into the soil under adjacent receivers is investigated in this paper for the first time. To this aim, simulations were carried out using a finite/infinite element model of a railway track, tunnel, and surrounding soil. A straightforward analytical approach was implemented to model the dynamic excitation of the moving train. In addition, the effect of a soft V-shaped grouted layer on vibration mitigation on the ground was evaluated via a parametric analysis that determined the impacts of soil type, grout specifications, and train speed. The obtained results clearly indicated that a softer isolator (i.e., the grouted layer) in combination with a stiffer soil provides the best configuration for attenuating the subway-induced vibrations. Furthermore, the injection angle and train speed were shown to have minimal impacts on the isolator performance. Other contributions of the present paper include developing a simple equation to estimate the grouted layer effectiveness and describing how the isolator works in layered soils.